KARAKTERISTIK PENDERITA KOLELITIASIS YANG DIRAWAT INAP DI RUMAH SAKIT SANTA ELISABETH MEDAN PADA TAHUN 2010-2011 - jojorita girsang (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2012)
Cholelithiasis is gallstone disease that can be found in the gladbladder or bile duct or in both.  At autopsy examination in the United States, gall bladder stone was found in 20% of women and 8% of men. Incidence of gallbladder stones in Indonesia is not yet known with certainty because there is no research. in Santa Elisabeth  Hospital Medan, proportion of cholelihiasis patients hospitalized in 2010-2011 was found 55,4% 0f men and 44,6% of women. In order to know the characteri stics of Cholelithiasis patients who were hospitalized in Santa Elisabeth  Hospital Medan, done descriptive research with case series design.  The population was 101. The sample size equal to the population. Data were analyzed using chi-square test and Kruskal Wallis. Proportion based on sosiodemografhy, highest age> 40 years old (63,4%),  male (55,4%), Bataknese (83,1%),  Protestant Christians (64,4%), employees (21,8%), and Medan (53,5%). Biliary colic (37,6%), gallstone size in diameter ≤2 cm (41,6%), the average length of cholelithiasis patients 5,67 days, non-surgical medical management (65,3%), medical dissolution (74,2%), patient went back with cure (54,4%). There was difference from the average length of cholelithiasis and the patient’s condition when check out from the hospital (p < 0,05). There was difference from medical management and the patient’s condition when check out from the hospital (p < 0,05). There was difference from the average length of cholelithiasis and medical management (p < 0,05). In women and men aged >40 years old had a risk for cholelithiasis therefore suggested to decreas  intake of saturated fat. In patients with post operative cholelithiasis advised to reduce fat intake. Santa Elisabeth hospital  suggested to complete the medical  record  especially for  occupation, size of gallstones, the gallstones, gallstones location, type of gallstones and indication in the implementation of surgical and non surgical. Keywords : Cholelithiasis, Characteristics of the patient, Santa Elisabeth Hospital.